Structural Behaviour of Cold Formed Steel Sections Based on Fasteners - S. Karthikeyan; K. M. Jeevananthan; T. Karis Prabakar; R. Harini; S. P. Murali Kannan (Techniques and Innovation in Engineering Research Vol. 6, 2022)
In developed countries, cold formed steel sections are widely utilized for a variety of purposes, including roofs in the form of deck sheeting and structural components like beams and columns. Cold formed steel is used very little in developing countries like India, where the market for traditional hot rolled steel sections is still growing. However, cold formed built-up sections can be employed for a variety of applications where spans are minimal and there are few active loads if they are produced effectively. This work examined the structural behavior of cold formed sections depending on various fastening types. We compare and analyze the behavior of cold-formed sections that are primarily supported by bolts and welding. It was investigated how different types of fasteners and their connection methods affected the strength of cold-formed sections. According to studies, changing the type of fasteners led to appreciable modifications in the behavior of similar members.